Áreas prioritárias para a conservação: um estudo da sociobiodiversidade estuarina do Rio Paraíba no Norte - Sousa, Viviane dos Santos (2017)
The Priority Areas for biodiversity conservation were created by the Ministry of the Environment as a conservation strategy, taking into account the concept of hotspots, that is, areas that concentrate high levels of biodiversity and greater anthropic pressure. In Paraíba, one of the priority areas is the Paraíba do Norte River Estuary, located in the middle portion of the coast, overlooking the cities of Cabedelo, Lucena, João Pessoa, Santa Rita and Bayeux. The region presents a set of associated ecosystems and an intense urbanization, consequently diverse socioenvironmental disturbances. The present study had as general objective to analyze the conservation of the sociobiodiversity of the estuarine region of the Paraíba do Norte river, based on the available literature and the interpretation of the social actors. The research was considered a Case Study, presented as methodological course bibliographic review, document analysis, interviews and field visits. It was characterized as qualitative research being descriptive and exploratory in a reflexive approach. For the qualitative phase, content analysis was adopted, as well as variables, categories and attributes. Regarding the results of the biodiversity analysis, it was generally found that the region presents a favorable condition for ecological balance according to the criteria of species diversity. However, there is a presence of exotic flora and fauna, which does not yet represent a state of ecological vulnerability, but is concerned that one of the fauna species is overexploited, as is the case of crab-uca, a species used as an extractive resource. Of self-consumption of the traditional communities of the estuary, a fact that directly affects sociobiodiversity. For the analysis of socio-biodiversity, it was verified that on public policies in the interpretation of social actors presents unfavorable conditions regarding its effectiveness. In relation to the state of conservation, they also signal conditions unfavorable to the ecological balance. And as for the changes in local biodiversity, it has shown a lack of conservation, in this way decommissioning with ecological balance. Regarding the primary productive base and the traditional knowledge presented unfavorable conditions regarding local satisfaction and ecological balance. The need for an integrated management of municipalities, as well as participatory actions of local social actors to elaborate and implement policies for socio-biodiversity, and stimuli for local productive arrangements that stimulate and conserve traditional knowledge.